Pengaruh PDRB dan Upah Minimum Provinsi Terhadap Penyerapan Tenaga Kerja Melalui Mediasi Investasi di Provinsi Bali - Budiarto, Arif; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Employment issues one of which can be reduced by increasing economic growth is one indicator of the success of development. Economic growth in an area depends on many factors, one of which is the government policy itself. This study aimed to analyze the effect of directly or indirectly GDP and provincial minimum wage to investment and employment in the province of Bali. The analysis technique used in this study is the technique of path analysis. Results of the analysis of the data showed that GDP significant positive effect on investment and the employment rate. The minimum wage negative but no significant impact on investment and employment. Investments significant negative effect on employment. Investment is not a mediating variables influence the provincial minimum wage on employment and not the mediating variables influence of GDP on employment.
Keywords: GDP; the provincial minimum wage; investment; employment